Social media as a means for students to become global citizens - Matang, Matang; Sapriya, Sapriya; Suryadi, Karim; Darmawan, Cecep; Anggraeni, Leni (Program Pascasarjana Universitas Negeri Yogyakarta, 2023)
The development of information technology, especially social media, has paved the way for the theory and concept of global citizenship. Integration and connection allow everyone to convey citizens' opinions, ideas, criticism, and actions. Based on the literature and previous studies, social media is analyzed in terms of benefits and disadvantages. This study aims to emphasize the use of social media among students, especially as a means of becoming global citizens. This research was conducted using qualitative methods by analyzing various literature and sources, which were then described. The study results a show that student activity in social media contributes to a new media ecology called global citizen solidarity in social media. Student solidarity in viewing various problems that occur led to civic action. Student actions on social media in various fields and issues on global issues such as politics, religion, economy, environment, health, philanthropy, and human rights reinforce the concept of being global citizens. The transformation regarding the use of social media by students into a theoretical framework for global citizen practice. It is important to re-describe the concept of global citizenship or cosmopolitanism through social media to create world citizen solidarity as a sense of responsibility in dealing with global problems and promoting world peace.